Prevalence of scoliosis and impaired pulmonary function in patients with type III osteogenesis imperfecta - Keuning, M. C.; Leeuwerke, S. J. G.; van Dijk, P. R.; Harsevoort, A. G. J.; Grotjohan, H. P.; Franken, A. A. M.; Janus, G. J. M. (European spine journal, 2022)
Purpose Osteogenesis Imperfecta (OI) is a rare group of congenital genetic disorders that consists of a collagen synthesis defect. The most severe phenotype is type III OI. Characterized by progressive bone deformity, fragility and pulmonary impairment, causing significant morbidity and mortality. Also, multilevel spine deformities are observed, such as scoliosis. The literature on the pathophysiology of pulmonary impairment in relation to scoliosis in these patients is scarce and conflicting. This study aims to determine the prevalence of scoliosis and its relation to pulmonary function in type III OI patients. Methods This retrospective cohort study took place between April 2020 and November 2021. Forty-two patients with type III OI were included. Anterior–posterior spine radiographs were evaluated for scoliosis. Pulmonary function was assessed using spirometry and partial pressure of carbon dioxide. Results All 42 patients had scoliosis, with a mean curve of 66° (95% CI of range). Vital lung capacity was decreased, compared to a non-OI population (mean 1.57 L). This was correlated to the degree of scoliosis (st. β − 0.40, P = 0.03), especially in increasing thoracic curves. Restrictive lung pathophysiology was shown in our study population with a mean FEV1/FVC ratio of 0.85. Conclusions Increasing thoracic scoliosis was correlated with decreased vital lung capacity in our study population of type III OI patients. High FEV1/FVC ratios found in this study population show restrictive lung pathophysiology. Therefore, it is plausible that the pulmonary impairment found in type III OI patients is a combined issue, partly associated to scoliosis and partly intrinsic to OI.